2012
DOI: 10.1387/ijdb.120136pw
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the zona pellucida of the mouse egg on folliculogenesis and fertility

Abstract: All mammalian eggs are surrounded by a relatively thick extracellular coat, called the zona pellucida (ZP), that plays vital roles during oogenesis, fertilization, and preimplantation development. The mouse egg ZP consists of three glycoproteins, called mZP1-3, that are synthesized solely by oocytes during their 2-to-3 week growth phase. The ZP is seen initially as isolated extracellular deposits of nascent ZP fibrils that coalesce to form a thickening matrix. Elimination of ZP glycoprotein synthesis by target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…6, 7 After sperm-egg fusion, the ZP undergoes ‘hardening,’ which prevents further sperm binding and is referred to as the block to polyspermy. 810 Following fertilization and transit of the early embryo through the oviduct and the uterus, the zona pellucida serves as a protective barrier between the developing egg and zygote and the external environment. 10, 11 The ZP provides a rigid and defined volume for the dividing zygote as it proceeds through numerous cell divisions during pre-implantation embryo development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6, 7 After sperm-egg fusion, the ZP undergoes ‘hardening,’ which prevents further sperm binding and is referred to as the block to polyspermy. 810 Following fertilization and transit of the early embryo through the oviduct and the uterus, the zona pellucida serves as a protective barrier between the developing egg and zygote and the external environment. 10, 11 The ZP provides a rigid and defined volume for the dividing zygote as it proceeds through numerous cell divisions during pre-implantation embryo development.…”
Section: Introductionmentioning
confidence: 99%
“…10, 11 The ZP provides a rigid and defined volume for the dividing zygote as it proceeds through numerous cell divisions during pre-implantation embryo development. 9, 10 …”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in the ZP can lead to failure of fertilization, implantation, and pregnancy [17], [18]. Mouse ZP is comprised of three types of glycoproteins: ZP1, ZP2, and ZP3 [19]. A recent study showed that oocytes lacking, or with incomplete synthesis of, ZP1, ZP2, or ZP3 cannot be fertilized [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…Presence of ZP2 (A) and ZP4 (B) transcripts was evaluated by RT-qPCR analysis MFCS = oocytes isolated from medium follicles of cycling sows, SFJG = oocytes from small follicles of juvenile gilts, SFCS = oocytes from small follicles of cycling sows Results are presented as mean ± SEM with the level of significance of P < 0.001 (*P < 0.01) a-c values with different superscripts are significantly different secondary sperm receptors, playing a significant role in gamete fusion during successful monospermic fertilization (Topfer-Petersen 1999). It has been previously shown in several species that oocytes lacking ZPs proteins are unable to fertilize (Harada et al 2003;Wassarman and Litscher 2012;Huang et al 2014). Ovarian follicle size significantly influences the ability of oocytes to mature and the gamete fertilizability.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that the structure and expression of ZPs significantly influence the first recognition, interaction, and fusion between female and male gametes (Chiu et al, 2008;Wassarman and Litscher 2012;Avella et al 2014). Therefore, ZPs are recognized as the most important markers of fertilization ability of mammalian oocytes.…”
Section: Doi: 1017221/90/2016-cjasmentioning
confidence: 99%